Executive Committee Minutes 2010-05-06 - Academic Senate:::::::::
Program Track in ELSE for Communication Development, Revision to Specialist Program in ELSE, Revision to English Single Subject Credential, New Minor in Queer Studies, Online forum concerning the financial management of SSU, Faculty Representation on Administrative Appointment Committees policy, Changes to Structure and Functions in the by-laws, Revision to WEPT policy